Three case reports with synthetic cannabinoids and their clinical reflection: a review - Altıntaş, Merih; İnanç, Leman; Güleç, Hüseyin (Journal of Dependence, 2016)
Synthetic cannabinoids (SCs) have become a problem of public health and security nowadays. Their use has increased especially among young people both in the world and in our country. Synthetic marijuana varieties have many names such as Bonsai and Jamaica being the most popular in Turkey. The cheapness and easy accessibility of these drugs cause their widespread popularity. SCs cannot be detected with current screening tests, because their pharmacological formulations are often changed by the drug designers. The heterogeneity of their ingredients makes it difficult to predict the clinical picture. These drugs can affect multiple systems with life threatening consequences presenting varying clinical views. After SC consumption, SC users complain of physiological and psychiatric symptoms resulting in applying to emergency rooms, psychiatric clinics and family physicians. This situation has become worrisome for many health practitioners. There is a need for a multidisciplinary approach for recognition, intervention and treatment of the clinical manifestation resulting from SC use.
Keywords: Bonsai; Jamaican gold; synthetic cannabinoid